TRANSFORMASI PENDIDIKAN ISLAM DALAM LINGKUP DIMENSI SOSIO-KULTURAL DI PONDOK PESANTREN DAARUL HUDA CIAMIS - Fenty Setiawati; Fazar Rifqi As Sidik; Euis Erha Rohmah Hamidah; Fadhilah Anggraini Pane; Mohamad Erihadiana (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study examines the transformation of Islamic education within the socio-cultural dimension at Daarul Huda Islamic Boarding School in Ciamis. The transformation includes curriculum changes, teaching methods, and the integration of socio-cultural and multicultural values into education. Using a qualitative approach and case study design, the study finds that Daarul Huda Islamic Boarding School successfully integrates religious knowledge with general science and technology without neglecting traditional values and local culture. The kyai plays a pivotal role in leading this transformation, balancing tradition and modernity. However, resistance to change among certain pesantren circles poses significant challenges. The findings demonstrate that Daarul Huda Islamic Boarding School has created an inclusive education system, relevant to contemporary developments while maintaining strong local and religious values. These results contribute to the development of Islamic education that adapts to socio-cultural changes.